Whole cigarette smoke condensates induce ferroptosis in human bronchial epithelial cells - Park, Eun-Jung; Park, Yoo-Jin; Lee, Sang Jin; Lee, Kyuhong; Yoon, Cheolho (Toxicology letters, 2019)
Cigarette smoke is responsible for many fatal pulmonary diseases, however, the toxic mechanism is still unclear. In this study, we first confirmed that whole cigarette smoke condensates (WCSC) contain hydrophilic elements, lipophilic and gaseous components. Then, we treated BEAS-2B cells, a normal human bronchial epithelial cell line, at dosages of 0.25, 0.5, and 1% for 24 h and explored the toxic mechanism. Cell viability decreased in a dose-dependent manner, and fission and fusion of mitochondria, damage of endoplasmic reticulume (ER) structures, and formation of autophagosome-like vacuoles were found in cells treated with 1% WCSC. Mitochondrial and ER volumes, lysosomal fluorescence intensity, LDH release, and intracellular ROS levels notably decreased at the highest doses compared with the control, whereas intracellular calcium ion and NO levels were significantly elevated accompanying G2/M phase arrest. Expression of an iron-binding nuclear protein-related gene (pirin) was the most up-regulated in the WCSC-treated cells with enhanced expression of antioxidant-related genes, whereas expression of carbonic anhydrase IX gene, a marker of tumor hypoxia, was the most down-regulated. Additionally, levels of apoptosis (BAX, Apaf-1, and cleavage of caspase-3 and PARP), autophagy (p62 and LC3B-II), ER stress (PERK, IRE-1a, Bip, and CHOP), antioxidant (SOD-1 and SOD-2), and MAPkinase activation (p-ERK, p-p38, and p-JNK)-related proteins were clearly enhanced following exposure to WCSC, whereas expression of several mitochondrial dynamics-related proteins was reduced with dose. Interestingly, expression of ferritin protein (light chain) was dramatically enhanced near the ER along with that of p62 protein. More importantly, the hypoxia inducible factor-1 pathway and ferroptosis were proposed among the 20 terms in KEGG pathway analysis, and secretion of IL-6 and IL-8, which are involved in hypoxia-induced inflammation, were clearly elevated with dose. Taken together, we suggest that WCSC may induce ferroptosis in bronchial epithelial cells via ER stress and disturbed homeostasis in mitochondrial dynamics caused by induction of hypoxia conditions.